2000
DOI: 10.4049/jimmunol.165.2.1066
|View full text |Cite
|
Sign up to set email alerts
|

Distal Recognition Site for Classical Pathway Convertase Located in the C345C/Netrin Module of Complement Component C5

Abstract: Previous studies focused on indels in the complement C345 protein family identified a number of potential protein-protein interaction sites in components C3 and C5. Here, one of these sites in C5, near the α-chain C terminus, was examined by alanine-scanning mutagenesis at 16 of the 18 non-alanine residues in the sequence KEALQIKYNFSFRYIYPLD. Alanine substitutions affected activities in the highly variable manner characteristic of binding sites. Substitutions at the lysine or either phenylalanine residue in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Studies by Jelezarova et al (31) have suggested C3b-C3b dimers in complex with IgG molecules to form better precursors of convertases than C3b. Recent studies by Sandoval et al (32) involving indels have identified at least two binding sites on C5 for the classical pathway C5 convertase in addition to the convertase cleavage site. Based on all these studies it appears that C5 binds with high affinity to multimeric C3b complexes through interactions of at least two distinct sites on C5 and at least two sites on C3b.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Jelezarova et al (31) have suggested C3b-C3b dimers in complex with IgG molecules to form better precursors of convertases than C3b. Recent studies by Sandoval et al (32) involving indels have identified at least two binding sites on C5 for the classical pathway C5 convertase in addition to the convertase cleavage site. Based on all these studies it appears that C5 binds with high affinity to multimeric C3b complexes through interactions of at least two distinct sites on C5 and at least two sites on C3b.…”
Section: Discussionmentioning
confidence: 99%
“…In that case mutations of the DE loop might disrupt the arrangement of domains within the full-length protein and exert their functional influence indirectly. Arguing against this, however, is the observation that a peptide extending from Lys 1604 to Arg 1616 inhibited complement hemolytic activity and activation of C5 by the convertase pathway C5 convertase (but not cobra venom factor) (17). Furthermore, the consequences for inhibitory activity of alanine substitution within the peptide reflected the results of alanine-scanning mutagenesis in C5.…”
mentioning
confidence: 98%
“…2), and the interaction with C7, but not C6, appears to be essential for the nonreversible formation of the MAC. 2 The F1613A mutant used in the current structure determination retained the ability to bind C6 and C7 (Table I); indeed, none of several DE loop mutations in C5 influenced binding to C6 (17). Therefore, the C6/C7-binding site of C5-C345C is likely to lie elsewhere.…”
mentioning
confidence: 99%
See 2 more Smart Citations